Mathematical modeling of drug release from swellable polymeric nanoparticles - Soha Azadi & , Hajar Ashrafi & , Amir Azadi & (Journal of Applied Pharmaceutical Science, 2017)
This study aims to provide a comparative mathematical analysis of drug release from swellable polymeric delivery systems to find a general model applicable to multi-mechanistic release. Drug release data from various swellable polymeric nanoparticles extracted from the literatures were applied to the eight conventional models. Coefficient of determination (R2) and absolute percent error (E%) were calculated for each set as well as the overall error (OE), the number of error (NE) and the akaike information criterion (AIC) for all sets. The model has the highest R2 and the number of the error, as well as both the lowest overall error (OE) and the akaike information criterion, was considered as the best one. Among the models Weibull (W) model produced R2 and OE values of 0.93 and 8.79, respectively. Also, the AIC value and the number of errors less than 5% for the model was -34.93 and 46.15% of a total number of data sets respectively. Mathematical modeling of drug release from a carrier is often attempted to recognize the main determinants of the drug release rate from the carrier with the final goal of the identification of the ideal set of conditions leading to the desired release profile in vivo.
Keywords: Mathematical modeling, drug release, swellable polymeric nanoparticles, nanotechnology, polymeric nanoparticles.